Procurement Ethics and Accountability: A Comparative Analysis of Government and Private Sector Practices in the Philippines - Orencia, Abrian Joy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Procurement has always mirrored how institutions value fairness and discipline. In the Philippines, a major turning point came with the transition from Republic Act 9184 to RA 12009. This reform renewed the government’s push for transparency and digital integration while encouraging professionalism among procurement staff. The private sector, though ruled by its own internal frameworks, faces a similar public demand to demonstrate ethics and accountability. Few studies, however, have looked at both sides in one frame. This study brought together 36 procurement professionals—half from government, half from private organizations—through a structured survey and 10 follow-up interviews. Their stories reveal the same ethical spirit but different approaches: government workers lean on compliance and transparency; corporate buyers emphasize efficiency and flexibility. Most welcomed RA 12009, though many said that paperwork, supplier diversity, and training remain persistent hurdles. Despite these, both sectors show readiness to learn from one another, particularly in ethics, documentation, and digital systems. The research points to one message: integrity thrives best when systems are clear, people are trained, and collaboration is encouraged.